Extension Program and Customer Satisfaction: Are We Serving All Clients Well? - Sebastian Galindo-Gonzalez; Glenn D. Israel; Marna Weston; Kathryn A. Israel (EDIS)
AEC-389, a 5-page illustrated fact sheet by Sebastian Galindo-Gonzalez, Glenn D. Israel, Marna Weston, and Kathryn A. Israel, explores whether race or gender have an effect on the perceptions of the clientele regarding the quality and outcome of services provided by Extension. Includes references. Published by the UF Department of Agricultural Education and Communication, May 2008.